The Use of Phpmailer in E-SPT System (Electronic Task Order) Parking Court at The Transportation Office Bengkulu City - Pahrizal Pahrizal; Muntahanah Muntahanah; Yuza Reswan; Widia Seprianti (Jurnal Komputer, Informasi dan Teknologi, 2022)
Parking attendants or parking attendants who are also known as judges are people who work to help regulate vehicles entering and leave the parking lot. In carrying out its activities, the parking attendant must have a parking attendant's duty order (SPT). The problems with the parking attendant’s duty warrant is that the registration process for prospective parking attendants is still done manually, the SPT is still being made and typed one by one, and the parking attendant duty warrant is not in the form of a clerk’s duty which is not in the form of a clerk. Seeing this problems, the author provides a solution, namely by creating a website-based parking attadant E-SPT system. E-SPT or can be called an electronic assignment warrant is one type of electronic letter in digital form that is obtained using the internet. In the E-SPT system, the parking attendant will make it easier to manage SPT. Then this system uses PHPMailer to make it easier to send E-SPT data to the parking attendant's email. The results of this study have been made a website-based E-SPT system for parking attendants.